Autoimmune cytopenias associated with inflammatory bowel diseases: Insights from a multicenter retrospective cohort. Issue 4 (April 2017) - Uzzan, Mathieu; Galicier, Lionel; Gornet, Jean-Marc; Oksenhendler, Eric; Fieschi, Claire; Allez, Matthieu; Bouhnik, Yoram; Kirchgesner, Julien; Boutboul, David; Treton, Xavier; Gérard, Laurence; Mahévas, Matthieu; et al.
Abstract: Introduction: Autoimmune cytopenias (AIC) including autoimmune hemolytic anemia (AIHA) and immunologic thrombocytopenia (ITP) are rare immunologic disorders, scarcely reported in inflammatory bowel diseases (IBD). We conducted a multicentric retrospective study, including a case-control analysis, that aimed to describe the characteristics and outcomes of patients affected by AIC and IBD. Method: Forty cases were recruited from 4 IBD centers and 2 AIC tertiary centers. Controls were recruited from the MICISTA registry. Results: From the MICISTA registry, incidences were estimated at 4.1/100, 000 patient-years and 12.5/100, 000 patient-years after IBD diagnosis for AIHA and ITP, respectively. All AIHA patients (n = 14) had colonic involvement (13/14 with UC), whereas CD (52%) and UC (48%) diagnoses were evenly distributed among ITP patients. Compared to control IBD patients, cases were characterized by a higher frequency of extra-intestinal manifestations (37.5% vs 17%, p < 0.001) and by the presence of IBD severity's hallmark. AIHA and IBD ran mainly in parallel, and 12 out of 14 AIHA were warm AIHA. In isolated cases, rituximab and infliximab were efficient to treat IBD and AIC, respectively. IBD surgery may induce AIC remission in some cases. Conclusion: Although low, incidence of AIC appears higher in IBD patients compared to the general population. The association seems to be mainly non-fortuitous, especially for colitis-associated AIHA.